2021
DOI: 10.1364/boe.434465
|View full text |Cite
|
Sign up to set email alerts
|

Label-free automated neutropenia detection and grading using deep-ultraviolet microscopy

Abstract: Neutropenia is a condition identified by an abnormally low number of neutrophils in the bloodstream and signifies an increased risk of severe infection. Cancer patients are particularly susceptible to this condition, which can be disruptive to their treatment and even life-threatening in severe cases. Thus, it is critical to routinely monitor neutrophil counts in cancer patients. However, the standard of care to assess neutropenia, the complete blood count (CBC), requires expensive and complex equipment, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…While several virtual staining techniques based on a variety of label-free imaging techniques have been presented [29][30][31][32], they are mostly geared toward the staining of tissues for histopathology and are not designed to digitally stain and analyze blood smears. Further, our segmentation method is robust and achieves comparable or even better performance than methods based on stained or pseudocolorized images, without the need for fix-ing and staining the sample [36][37][38] or the need for multispectral imaging [24]. We have presented a simple and robust classification and counting procedure that utilizes cellular and nuclear segmentation masks along with the grayscale images to first exclude dead WBCs and then classify healthy WBCs into five subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…While several virtual staining techniques based on a variety of label-free imaging techniques have been presented [29][30][31][32], they are mostly geared toward the staining of tissues for histopathology and are not designed to digitally stain and analyze blood smears. Further, our segmentation method is robust and achieves comparable or even better performance than methods based on stained or pseudocolorized images, without the need for fix-ing and staining the sample [36][37][38] or the need for multispectral imaging [24]. We have presented a simple and robust classification and counting procedure that utilizes cellular and nuclear segmentation masks along with the grayscale images to first exclude dead WBCs and then classify healthy WBCs into five subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected from 23 individuals (4 healthy donors, 4 patients suffering from sickle cell disease, 4 patients with thrombocytopenia, and 11 patients with neutropenia). 26 All protocols were approved by the Institutional Review Boards of Georgia Institute of Technology and Emory University, and informed consent was obtained from the donors. Imaging was performed after drying the samples in air for five minutes.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…20 We were also able to obtain a five-part WBC differential by leveraging structural and molecular information from segmented cells at 260 nm alone (having inherent nuclear contrast due to the absorption peak of nucleic acids). 20,26 Motivated by this, we developed a deep learning-based automated hematology analysis framework that operates on single-channel UV images acquired at 260 nm, enabling simpler instrumentation and a factor of three improvement in imaging speed without sacrificing accuracy. 22 Our automated pipeline consists of semantic segmentation of WBCs in grayscale images followed by 5-class WBC classification with an accuracy 94.02% on unseen test data.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies demonstrated UV microscopy for biomolecular mass-mapping in live cells without observable photodamage [7,9,10]. Recently applications of UV microscopy have included hematology analysis of whole blood samples and label-free histopathology of prostate cancer sections and fresh brain tissue [11][12][13][14][15][16][17]. In addition, live single-cell imaging with UV microscopy has been demonstrated for analysis of intracellular dynamics in cancer cells and T-cell phenotyping [18].…”
Section: Introductionmentioning
confidence: 99%